2009
DOI: 10.1007/s12022-009-9074-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Fine Needle Aspiration and Fine Needle Non-Aspiration Biopsy on Suspected Thyroid Nodules

Abstract: Ultrasonography-guided fine needle aspiration (FNA) and fine needle non-aspiration (FNNA) biopsy were performed consecutively on 104 patients (mean age 50 +/- 15 years) affected by multinodular and uninodular goiter. Both techniques were executed on the same patients in the same clinical session beginning with the first (FNA) on half of the patients (randomly selected) and vice versa. The cytological findings on cell samples were divided into four groups: colloidal (benign), follicular (suspicious), malignant,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 28 publications
2
30
1
Order By: Relevance
“…Kamal MM et al, [15] had statistically significant difference for the parameter of 'amount of cellularity'. Romitelli F et al, [14] reported statistically significant result only in case of number of inadequate smears, which were more by aspiration technique. In studies by Mair S et al, [10] and Maurya AK et al, [18] there was no statistically significant difference in the two techniques.…”
Section: Limitationsmentioning
confidence: 92%
See 2 more Smart Citations
“…Kamal MM et al, [15] had statistically significant difference for the parameter of 'amount of cellularity'. Romitelli F et al, [14] reported statistically significant result only in case of number of inadequate smears, which were more by aspiration technique. In studies by Mair S et al, [10] and Maurya AK et al, [18] there was no statistically significant difference in the two techniques.…”
Section: Limitationsmentioning
confidence: 92%
“…Order of Sampling: In our study for all the 200 cases we performed first FNS technique followed by FNA. In the study by Mair S et al, [10] and Romitelli F et al, [14] and Kamal MM et al, [15] in half cases they performed FNA technique first and vice-versa and came up with the result that there was no statistically significant difference between the scores of FNA and FNS whether performed as the first or second technique.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas other observed a statistically significant difference in the total score in favour of non -aspiration as compared with aspiration technique, FNNAC producing a better quality of specimen. (10,11) In the present study, more diagnostically superior and less diagnostically adequate sample were obtained more by non -aspiration technique in comparison to aspiration technique. It was observed that the percentage of inadequate sampling was more with non -aspiration (38%) than with aspiration (34%) technique in contrast to the observations of Santos and Leiman (4) and Ciatto et al (12) .…”
Section: Resultsmentioning
confidence: 45%
“…There is another technique, however, fine needle capillary (FNC) sampling/ fine needle non-aspiration cytology (FNNAC) which avoids aspiration but still permits cytologic review of the masses. This technique depends solely on capillary action of the fine needle, therefore is less painful, less traumatic and thus much more patient friendly (4).Several studies have reported conflicting results between FNAC and FNNAC (5,6,7). Some studies have reported that FNNAC produces better specimens for cytological diagnosis (7).…”
Section: Introductionmentioning
confidence: 99%